Avaliação de usabilidade de manequim de simulação de alta fidelidade e guia de ressuscitação cardiopulmonar no ensino de estudantes de medicina do IMEPAC Araguari - Silva, Lucas de Brito (2023)
The increase of the number of cardiac arrests in non-critical areas highlights the need for adequate training of all healthcare professionals, as patient survival directly depends on the skills of these professionals to perform high-quality cardiopulmonary resuscitation maneuvers. Simulation is a widely recognized method in the literature for teaching basic life support, including cardiopulmonary resuscitation. It provides students with the opportunity to apply clinical skills and make decisions in real-life situations without compromising patient wellbeing. In this context, simulation mannequins emerge as a more viable option for teaching and training cardiopulmonary resuscitation when compared to cadaver or live patient training. However, it is crucial to assess the quality of these mannequins in terms of their usability, which encompasses various properties and attributes derived from different methods of investigating human-machine interaction. To ensure the usability of a system, usability evaluation methods can be employed throughout the life cycle, involving real, predefined, and meaningful tasks to assess the efficiency, effectiveness, and user satisfaction with the interaction. Building upon the presented context and aiming to analyze the usability of a high-fidelity simulation mannequin, the general objective of this study is to evaluate the usability of a high-fidelity simulation mannequin used in the Realistic Simulation Center of IMEPAC (Instituto Master de Ensino Presidente Antônio Carlos) in Araguari, MG, for teaching cardiopulmonary resuscitation to medical students. The mannequin's usability evaluation utilized two tools: a data collection instrument developed based on the guide used by the Teaching Hospital for cardiopulmonary resuscitation instruction, and the SUS (System Usability Scale) questionnaire used for research feedback. Data collection took place at the Surgical Center of the IMEPAC Realistic Medical Simulation Center and involved one Instructor Professor to assist and instruct volunteer students, two Evaluating Professors to assess the performance of the volunteers using the mannequin, ranging from "Task not performed by the student" to "Task executed completely accurately," and 18 volunteer students who performed the predefined tasks and answered the feedback questionnaire. The results of this study demonstrate that the high-fidelity simulation mannequin is efficient and effective for teaching and/or training in cardiopulmonary resuscitation, as the average task scores ranged from 3.83 to 4.78, indicating "Had little difficulty in performing the task." User satisfaction measured by the SUS questionnaire indicated that the volunteers are not completely satisfied with the mannequin, as they agreed with the statement that they need specialized technician instruction to perform the tasks. Based on the results of usability, effectiveness, efficiency, and satisfaction evaluations, it can be concluded that users have a positive acceptance of the simulation mannequin. As a contribution to society and the academic community, the identification of areas for improvement in the mannequin is noteworthy, highlighting points of enhancement to be considered in the airways and chest.